The IoT Energy Monitoring System (EMOSY) using energy scavenging concept / Nur Amalina Muhamad ... [et al.] - Muhamad, Nur Amalina; Othman, Norhalida; Mat Saat, Ezril Hisham; Abdul Rahman, Noor Hasliza; Abdul Majid, Masmaria (Universiti Teknologi MARA Cawangan Pulau Pinang, 2022)
The adoption of an energy monitoring system to give customers information on their electricity consumption has received a lot of attention. Many technological solutions are now available due to advancements in electronics and computing. These solutions are important elements of a longterm future. Furthermore, with the rapid growth of information technology, particularly IoT, a better energy monitoring meter may be created by delivering real-time consumption data. This paper shows the development of a low-cost energy monitoring system which can store, analyze and display comprehensive energy consumption data. The IoT Energy Monitoring System named as EMOSY is developed using the energy scavenging concept. The ambient stray electric field is collected and converted from energy to power consumption using voltage detection circuit and Node MCU (ESP8266) as the microcontroller to retrieve data from sensor nodes and transfer it to a server via the internet. The database revealed that the built energy monitoring system can record electrical signals, power consumption, and electricity bills easily. This meter was placed near to the electrical devices then the device was switched on and off. The data will be sent and saved into the database. MySQL is used for data manipulation in database management and a cloud-based platform for website support has been used to see a realtime overview of how power is being consumed daily. This system was aimed to raise customer awareness of their energy consumption patterns by collecting data on their usage and being informed of their power usage.